METHOD OF CONSIDERATION A CHANGEABILITY OF EXTERNAL ENVIRONMENT AS AN ALTERNATIVE METHOD OF SOCIO-ECONOMIC PROCESSES MODELING - Belz, Oleksandra (International Journal of Computing, 2014)
The method of design of economic dynamics in a variable environment, which enables to carry out arbitrary nonlinear transformation and describe the moments of change of properties of the system without the problem of attachment of models to the time factor.